(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Delvian, Hartanto A. 2022. Short Communication: Occurrence of arbuscular mycorrhizal fungi associated with Casuarina equisetifolia in saline sandy environment, North Sumatra, Indonesia. Biodiversitas 23: 2520-2525. Arbuscular mycorrhizal fungi (AMF) form a mutualistic association with plant roots to cope in the extreme environments including the saline and sandy soils in the coastal areas. In this study, the occurrence of AMF associated with Casuarina equisetifolia that has been planted for coastal rehabilitation located at Cermin Beach, North Sumatra was investigated including its abiotic-biotic interactions from topsoils (0-20 cm) to subsoils (20-80 cm). A total of 10 AM fungal morphotypes were documented with Glomeraceae as the dominant AM fungal taxa (9 morphotypes) and a Glomoid morphotype exists in all soil depths. The number of AMF spores decreased as soil depth increased following other environmental conditions such as pH, soil P availability and soil moisture based on the result of Pearson’s correlation test. The results showed a moderate-to-low level of biodiversity of AMF based on Shannon’s diversity index. The findings revealed the vertical distribution of AMF in a saline environment and supported the planting of C. equisetifolia which successfully recruited the indigenous AMF to form a symbiosis to thrive in the stressful environment.